2016
DOI: 10.1016/j.cell.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Amplitude Regulation via FBXW7-Targeted REV-ERBα Degradation

Abstract: Summary Defects in circadian rhythm influence physiology and behavior with implications for the treatment of sleep disorders, metabolic disease and cancer. Although core regulatory components of clock rhythmicity have been defined, insight into the mechanisms underpinning amplitude is limited. We show here that REV-ERBα, a core inhibitory component of clock transcription, is targeted for ubiquitination and subsequent degradation by the F-box protein FBXW7. By relieving REV-ERBα-dependent repression, FBXW7 prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 58 publications
6
140
1
Order By: Relevance
“…However, correlation coefficients of CgCry2 with other genes were globally low under L:D and D:D conditions (0.264 < ρ < 0.623) and discrepancies of results associated to the absence of zeitgeber (light regime) could suggest the presence of an additional regulation mechanism of CgCry2 , independent from the regulation associated to the complex CLOCK:BMAL. Many aspects of molecular clockworks in animals, especially in marine organisms, still needed to be unraveled and were highlighted by the recent discovery of a new regulation loop in vertebrates [51]. Moreover, exposure of oyster to D:D regime was associated with an increase of the proportion of oysters exhibiting ultradian period but the relationships between oyster behaviors and gene expressions appeared complex to explain since QPCR results were performed on gills samples from oysters exhibiting circadian and ultradian rhythms and could therefore mask or alter observed profiles of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, correlation coefficients of CgCry2 with other genes were globally low under L:D and D:D conditions (0.264 < ρ < 0.623) and discrepancies of results associated to the absence of zeitgeber (light regime) could suggest the presence of an additional regulation mechanism of CgCry2 , independent from the regulation associated to the complex CLOCK:BMAL. Many aspects of molecular clockworks in animals, especially in marine organisms, still needed to be unraveled and were highlighted by the recent discovery of a new regulation loop in vertebrates [51]. Moreover, exposure of oyster to D:D regime was associated with an increase of the proportion of oysters exhibiting ultradian period but the relationships between oyster behaviors and gene expressions appeared complex to explain since QPCR results were performed on gills samples from oysters exhibiting circadian and ultradian rhythms and could therefore mask or alter observed profiles of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…A coupled transcriptional loop involving REV-ERBα and ROR regulates circadian amplitude (Zhao et al, 2016). Additional CLOCK-BMAL1 inhibitors (Zhao et al, 2006; Duffield et al, 2009; Robles et al, 2010; Anafi et al, 2014) and post-transcriptional processes (Menet et al, 2012) also influence the circadian cycle.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has identified FBXW7 as an enzyme that ubiquitinates REV-ERBα and thereby regulates the amplitude of the circadian clock 116 . FBXW7-mediated ubiquitination is dependent on the CDK1-catalyzed phosphorylation of REV-ERBα at Thr275, and liverspecific knockout of Fbxw7 leads to dysfunction in glucose and lipid metabolism.…”
Section: Ptms Of Rev-erb Regulating Metabolismmentioning
confidence: 99%